Estudio de tiempos y movimientos para optimizar el proceso de producción de hilatura en la empresa Textiles La Escala S.A., ubicada en la ciudad de Quito, sector Cotocollao, período 2012 - Banda Chicaiza, Luis Manuel (2013)
This research was carried on “La Escala” Textiles Company SA, in Quito city. It is a company dedicated to ring spinning, and spinning Jet development. The feedstock for this process is cotton and polyester. In this company there were no analysis of the activities of the operators in each section which are made of yarn production processes. Also, there were times between production sections and the lack of a standard time for performing various tasks accomplished by operators manually. This problem affects the tasks performed efficiently, and the productivity level expected of a normal working day. In this research field applied methodology and research techniques such as observation, facing each task analysis performed by all operators in each area, and the survey for staff supervision of all production activities spinning. Thereby using a time and motion analysis made in the areas of opening (540.79 min.) Stretching and bending (546.16 min.) Stretching and twisting (581.68 min.) Spinning (627.66 min.) and winding (549.52 min.) is indicated that these times they had to be improved to enhance the production index, a standardized time for the execution of some tasks that required an optimum time of operation. Finally, we determined the percentage yield in each section, and raised some alternatives especially cleaning tasks in each area, for operators in order to improve performance in the workplace.